Comparison of musculoskeletal pain among neuro-pediatric physiotherapist and orthopedic physiotherapist: an observational study - Rathod, Neelam K.; Diwan, Shraddha; Engineer, Palak M. (International Journal of Contemporary Pediatrics, 2022)
Background: Musculoskeletal disorders can affect the body's muscles, joints, tendons, ligaments and nerve which caused either by the work itself or by the therapist’s working environment. Physiotherapists routinely perform activities such as transferring dependent patients, assisting with mat activities, and lifting heavy equipment. These work tasks put therapists at risk for both acute and chronic musculoskeletal pain. Methods: An observational cross-sectional survey was carried out among 34 physiotherapists specialized as a neuro-pediatric and orthopedic PTs age more than 22 years old both male and females who are working as a full time PTs in clinic or a part time PTs (at least 4 hour/day with minimum 1 year work experience at same job) and not involved in any occupation other than physiotherapy (full/part time. Extended Nordic musculoskeletal questionnaire was used to quantify the musculoskeletal pain and activity limitation in 9 body regions. Results: Physiotherapist reported the highest rate of musculoskeletal disorder in the lower back and neck regions. During12-months period and point prevalence rate of WMSDs occurred mostly in low back region was (58.80%), neck (35.30%), upper back (35.30%) in neuro-paediatric physiotherapist and it was mostly in back region (41.10%) and neck, upper back, shoulder region (23.50%) respectively in orthopaedic physiotherapist. Conclusions: A high proportion of neuro-pediatric physiotherapist reported WMSDs at some body site working in their occupational lives with the low back pain and neck pain most often compare to orthopedic physiotherapists.